Federal Ownership of National and Dulles Airports : Background, Pro-Con Analysis, and Outlook. (U.S. Congressional Research., 1985)
Examines background and issues surrounding Administration proposal to transfer ownership of Washington National and Washington Dulles airports to a new regional airport authority. Addresses pros and cons of alternative actions available to Congress and the outlook for their possible implementation.